Achieving Circularity Through Novel Product-Service Systems in the Mining Industry: An Opportunity for Circularity - Vargas-Norambuena, J (Springer Nature, 2025)
The evolution toward sustainable mining can be achieved by implementing circular economies (CEs), and one way forward is via product-service systems (PSSs). However, applying PSSs in the mining industry is an area with little extant research. We seek to contribute to CE and sustainability research by proposing a model by which mining companies can achieve circularity through their suppliers: something which has not yet been explored. First, we present a critical literature review of published papers about the barriers and benefits in industries where servitization or PSS has been applied. We discuss barriers impeding PSS implementation in the mining industry, along with related concepts, including CE and PSSs in digital technologies. With this study, we hope to draw more discussion to the topic of PSSs in the mining industry and provide useful guidelines to academics and industry professionals for PSS implementation in mining: an important step toward circularity. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.